A TOOL FOR REFERENCE LIST GENERATOR - Mohd Kasirun, Zarinah (Malaysian Journal of Library and Information Science, 1997)
Reference List Generator is a tool to generate reference listings according to publishing styles that is chosen by a user. The five styles provided for are those prescribed by the American Psychological Association (APA), Chicago Manual, IEEE, the Modern Language Association (MLA) and Malaysian Journal of Computer Science. The target users are academicians and researchers who are involved in writing journal articles. RLG is a windows-based application implemented in Visual Basic Professional 4.0 which runs under the Microsoft Windows 3.1 environment platform. It exploits a modular programming model in its development and implementation. It can be incorporated as a tool to generate list of references in any word processor in future.